Cathedral at Durham
Another rebuilding of an east end, this time at Durham, afforded the additional space in the vicinity of the choir. The clustered piers of sandstone and Frostily vaults. It was also necessary to rebuild the final bay of the choir which had terminated in an apse, and the new feeling for enrichment can be seen in its triforium stage. The modern canopy marks the site of St. Cuthbert's shrine. All the masonry was executed in London and brought by sea to Durham.